2007
DOI: 10.1002/elps.200600434
|View full text |Cite
|
Sign up to set email alerts
|

Application of pressure cycling technology to tissue sample preparation for 2‐DE

Abstract: 2-DE is a powerful protein analytical tool whose major strengths include semiglobal quantitation and charge separation of complex protein mixtures, enabling the analysis of differential protein expression, and variable post-translational modification. One of 2-DE's limitations relates to its limited dynamic range and consequently the number of proteins expressed that can be analyzed on a single gel. In an attempt to improve the yield of detectable proteins during sample preparation, we applied a novel extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…PCT was performed using the Barocycler NEP-3229 instrument, disposable polypropylene PULSE Tubes FT-500 and the services of Pressure Biosciences (West Bridgewater, MA) as a research gift. The process was performed following suitable modification of standard protocol [18,19,21] for 60 cycles. Each cycle consisted of 20 s at 35 000 psi, followed by an instantaneous drop to atmospheric pressure and holding recovery.…”
Section: Pctmentioning
confidence: 99%
“…PCT was performed using the Barocycler NEP-3229 instrument, disposable polypropylene PULSE Tubes FT-500 and the services of Pressure Biosciences (West Bridgewater, MA) as a research gift. The process was performed following suitable modification of standard protocol [18,19,21] for 60 cycles. Each cycle consisted of 20 s at 35 000 psi, followed by an instantaneous drop to atmospheric pressure and holding recovery.…”
Section: Pctmentioning
confidence: 99%
“…Several techniques have been described to ‘crack’ worms, but each suffers from one or more limitations. Pressure Cycling Technology (PCT) uses expensive equipment to expose samples to multiple rounds of combined freezing, mechanical shearing and elevated hydrostatic pressure (40 cycles 35,000 psi) [6; 28]. Complete disruption of all worm stages, including dauers, can be accomplished using this procedure but it requires mixing of animals with a SiC abrasive [29].…”
Section: Discussionmentioning
confidence: 99%
“…PCT provides a simple, fast, effective and reproducible process to release cellular contents from biological samples [26,27,28]. Previously, it has been shown that the use of PCT increased protein yields from E. coli , where PCT extracted 14.2% more total protein than using a standard bead mill [29,30]. Furthermore, 2-DE showed 801 protein spots in the PCT lysate, compared to 760 spots in the bead mill lysate [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 2-DE showed 801 protein spots in the PCT lysate, compared to 760 spots in the bead mill lysate [29]. In mammalian liver tissue, PCT isolated more protein, as well as unique proteins when compared to protein isolation using a Polytron or ground-glass (GG) homogenizers [30,31]. Szabo et al found that PCT-assisted glycan release resulted in the rapid release of asparagine-linked glycans from bovine ribonuclease B, human transferrin and polyclonal human immunoglobulin [32].…”
Section: Introductionmentioning
confidence: 99%